The critical thinking ability of indigenous students in West Papua based on their tribe - Utami, Aprilia N.; Triyanto; Nurhasanah, Farida (AIP conference proceedings, 2022)
This study aims to describe the critical thinking of grade 12 students reviewed from the origin of the tribe at one of the schools in Manokwari. There are five tribes that will be described, namely the Javanese, Makassar, Kei, Batak and Biak tribes. Critical thinking ability refers to five indicators that are identifying, understanding, applying, analyzing, and evaluating. The research uses a descriptive qualitative approach. The main instrument is the researcher, with auxiliary instruments in the form of tests and interview guidelines. Through tests, interviews, and documentation, the data on this study was obtained. The study subjects were selected using snowball sampling, then the data was analyzed using the Miles and Hubberman methods, the validity of the data viewed by triangulation of methods and sources. The results showed that the critical thinking ability of students from Java is the same as the Batak tribe that meets the first to fourth indicators, the Makassar tribe meets all of the five indicators, the Kei meets the third indicator, and the Biak tribe meets the first and second indicators.